Applicability and development of a direct method algorithm for simultaneous optimization of trajectories and energy minimizing control for hybrid fuel cell railway vehicles. (May 2023) - Kühlkamp, Florian; Schenker, Moritz; Konrad, Marcel; Dittus, Holger
While the electrified rail network can directly utilize renewable energy sources, track electrification is costly and subject to environmental and structural limitations. Therefore, research is currently underway on alternative propulsion systems that enable overhead line-free operation. As a promising solution, the fuel cell electric drive came into focus as an emission-free drive system at the point of use. In order to be able to present a cost-efficient substitution of the propulsion systems in use today, an intensive examination of energy-optimal operating patterns, i.e. minimal fuel consumption, is crucial. This is the basis of this work, as it aims to develop an optimization algorithm that can handle fuel cell hybrid electric powertrains in a flexible and robust manner. The developed algorithm allows simultaneous optimization of the speed trajectory and on-board energy management with the aim of reducing hydrogen consumption. A comparison is made between a rule-based approach and the optimization algorithm. By simultaneously optimizing the trajectory and power distribution, 16% of the hydrogen savings potential can be achieved on a regional route in Germany compared to the rule-based approach. Finally, an in-depth evaluation of the algorithm's ability to flexibly handle different fuel cell hybrid powertrain topologies is performed. The results show that the optimization algorithm opens up the possibility of evaluating reasonable fuel cell hybrid component sizes while achieving optimal operation. Thus, it can be used in the future to support feasibility analysis for specific use cases.